Analisis T2 Turbo Spin Echo dengan GRAPPA dan Tanpa GRAPPA terhadap Kualitas Citra MRI Knee Joint Potongan Sagittal pada Klinis Metastatic Bone Disease - Dennis Kelana Putra; Wahyu Hidayat; Nurbaiti Nurbaiti (Poltekkes Kemenkes Semarang, 2026)
Background: Magnetic Resonance Imaging (MRI) is a diagnostic imaging modality that does not use ionizing radiation and offers high spatial resolution and excellent soft-tissue contrast, making it the primary modality for the evaluation of metastatic bone disease. In musculoskeletal examinations, particularly knee joint MRI, the sagittal T2 Turbo Spin Echo (TSE) sequence plays a crucial role in depicting bone involvement, bone marrow infiltration, and surrounding soft tissues in metastatic cases. This information is essential for assessing lesion extent and supporting accurate clinical diagnosis. In patients with metastatic bone disease, MRI examinations are often limited by severe pain, restricted mobility, and reduced patient tolerance to prolonged scan times. These clinical challenges necessitate the use of faster acquisition techniques without compromising diagnostic image quality. One technique developed to address this need is parallel imaging using Generalized Autocalibrating Partially Parallel Acquisitions (GRAPPA), which operates by undersampling k-space data to reduce acquisition time. However, the application of GRAPPA may influence image quality, thereby requiring objective and clinical evaluation. Methods: This study aimed to analyze differences in image quality, including anatomical structure information, image contrast and sharpness, and artifacts, in sagittal knee joint MRI using T2 Turbo Spin Echo sequences with and without GRAPPA in patients with metastatic bone disease. The study employed a quantitative analytic design with an experimental approach by comparing two acquisition techniques: sagittal T2 TSE imaging with GRAPPA and sagittal T2 TSE imaging without GRAPPA. Image quality assessment was based on contrast and image sharpness parameters, which were evaluated by professional respondents using a structured assessment instrument. The collected data were then statistically analyzed using the Wilcoxon test to determine differences in image quality between the two techniques. Results: the results demonstrated that the contrast and sharpness of knee joint MRI images acquired with GRAPPA are much better than those obtained without GRAPPA. This finding was supported by the Wilcoxon test (Z = −2.388; p = 0.017 < 0.05), indicating a statistically significant difference in image quality in the patients with metastatic bone disease. In addition, the use of GRAPPA in sagittal T2 TSE knee MRI also provided clear visualization of anatomical structures, with artifacts remaining within diagnostically acceptable limits, indicating that this technique is effective and comparable to non-GRAPPA imaging. Conclusions: The use of GRAPPA in sagittal T2 Turbo Spin Echo MRI of the knee joint provides significantly better image sharpness and contrast compared to non-GRAPPA imaging (Z = −2.388; p = 0.017). GRAPPA also enables clear visualization of knee joint anatomical structures with diagnostically acceptable artifact levels. Therefore, GRAPPA is an effective technique for improving anatomical image quality in knee MRI of metastatic bone disease.